2008
DOI: 10.1111/j.1365-2486.2008.01616.x
|View full text |Cite
|
Sign up to set email alerts
|

Sixty years of environmental change in the world's largest freshwater lake – Lake Baikal, Siberia

Abstract: High-resolution data collected over the past 60 years by a single family of Siberian scientists on Lake Baikal reveal significant warming of surface waters and long-term changes in the basal food web of the world's largest, most ancient lake. Attaining depths over 1.6 km, Lake Baikal is the deepest and most voluminous of the world's great lakes. Increases in average water temperature (1.21 °C since 1946), chlorophyll a (300% since 1979), and an influential group of zooplankton grazers (335% increase in cladoce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
253
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 324 publications
(272 citation statements)
references
References 51 publications
15
253
1
3
Order By: Relevance
“…3d; Table 1), indicating that air temperature was the dominant factor affecting water temperature. Such significant positive correlations have been widely observed in other lakes (Coats et al 2006;Hampton et al 2008;Adrian et al 2009). As water depth increased, the determination coefficient between air temperature and water temperature markedly decreased.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…3d; Table 1), indicating that air temperature was the dominant factor affecting water temperature. Such significant positive correlations have been widely observed in other lakes (Coats et al 2006;Hampton et al 2008;Adrian et al 2009). As water depth increased, the determination coefficient between air temperature and water temperature markedly decreased.…”
Section: Resultsmentioning
confidence: 61%
“…Previous studies have shown that regional-scale air temperatures and surface-water temperatures are highly correlated (Coats et al 2006;Hampton et al 2008;Adrian et al 2009). Thus, the air temperature increase caused by global climate change is anticipated to have a profound effect worldwide on aquatic ecosystems, including their chemical and physical properties and biotic and ecosystemscale responses.…”
mentioning
confidence: 99%
“…Recent studies have investigated the thermal characteristics of large lakes using a variety of methods, including direct, in situ measurements (Verburg et al 2003;Coats et al 2006;Hampton et al 2008), remote sensing techniques (Schneider et al 2009;Schneider and Hook 2010), and other sources, such as historical records of ice cover (Magnuson et al 2000). Collecting data in large lakes requires overcoming challenges not encountered when making measurements on land or in small lakes, and few time-series or other observations go back more than a few decades, (McCormick and Fahnenstiel 1999;Verburg et al 2003;Vollmer et al 2005).…”
mentioning
confidence: 99%
“…Arhonditsis et al 2004;Coats et al 2006;Austin and Colman 2008), East Africa (e.g. O'Reilly et al 2003;Verburg et al 2003), Siberia (Hampton et al 2008) and Antarctica (Quayle et al 2002). A recent study based on satellite thermal infrared images from 1985 onwards (Schneider and Hook 2010) confirmed that lake surface temperatures have been undergoing a long-term increase over large areas of the northern hemisphere.…”
Section: Climate Warming and Impacts On Lake Physicsmentioning
confidence: 87%